Effects of exhaust emissions from diesel engine applications on environment and health: a review - Jalaludin, Juliana; Jarkoni, Mohammad Nor Khasbi; Wan Mansor, Wan Nurdiyana; Abdullah, Samsuri; Che Wan Othman, Che Wan Mohd Noor; Abu Bakar, Anuar (Penerbit Universiti Malaysia Terengganu, 2022)
Recent achievements in Diesel Engine Applications (DEAs) have accomplished a very satisfactory level speeding up work, saving cost as well as energy. Tremendous research on its work mechanism have led to sustainable and renewable energy. DEAs significantly boost the economy and industrial sectors, which in turn provide comfort and improved lifestyle. Previous studies focused on the creative and innovative methods in diesel engine combustion process to reduce poisonous exhaust emissions. Looking beyond it advances, the exhaust emissions from DEAs contribute to climate change and global warming. The highlighted emitted gasses are oxides of nitrogen (NOx), carbon monoxide (CO) and hydrocarbon (HC), all of which are known to be among the greenhouse gasses (GHG). Particulate matter (PM) from DEA exhaust is also taken into consideration in the study. Exhaust emission mainly comes from the fossil fuel combustion and may come from natural sources. This study explores the effects of exhaust emission on the environment and health. Adverse effects of exhaust emissions on health are mostly related to cardiovascular and respiratory diseases. Climate change and global warming resulting from exhaust emissions also have disastrous consequences. Excessive and uncontrollable exhaust emissions increases global temperature and create a cycle of disasters, such as drought, fire and rising seawater level, causing floods in lowland areas. Although DEAs simplify our work and give a lot of benefits, they also adverse have implications on humans and the environment.